De-naturalizing antagonistic nationalism through an academic intervention: The reception of two photography exhibitions on the memorialization of the Cyprus Problem - Carpentier, Nico; Doudaki, Vaia; Christidis, Yiannis; Köksal, Fatma Nazli (My University, 2018)
© 2018 Vita e Pensiero. The article evaluates an academic intervention which consisted out of two photography exhibitions in Cyprus, focussing on the memorialization of the Cyprus Problem. These exhibitions communicated academic research into antagonistic nationalism and aimed to trigger societal debate, empowering the more agonism-oriented parts of society, and offering opportunities for reflection to others, simultaneously acknowledging the limits one intervention has. The article starts with reflections on academic interventions and on the agonization of conflict, and then describes the two exhibitions and the intervention's objectives. The reception component, which is the heart of the analysis, first shows the considerable reach the intervention had, and then discusses how the visitors argued for the analytical and critical relevance of the exhibitions, how they problematized (parts of) the exhibitions and how they triggered new signifying practices (after the exhibitions). Finally, the conclusion critically reflects on the de-naturalizing strategies of the intervention.
Keywords: Agonism; Conflict; Cyprus Problem; Exhibition; Intervention; Photography; Reception